Economic and financial feasibility in sugar cane production in small farms - Santos, David Ferreira Lopes [UNESP]; Mendes, Catherine Carnio [UNESP]; Borba De Moraes Farinelli, Juliana [UNESP]; Farinelli, Rogério (My University, 2016)
This study analyzes the economic and financial viability in the production of sugarcane in small farms in the region of Jaboticabal-SP, through the cost-volume-profit analysis model (CVP) with Discounted Cash Flow (DCF). The material that supported the research was gathered from the reality of a farmer, in particular, in order to evaluate the proposed model, considering planting to harvest 2014/2015. Exploratory-descriptive analysis of this material was achieved through qualitative and quantitative approach combined with the use of CVP and DCF analysis. The results report that there is a positive contribution margin in the sugarcane growth, but the operational, financial and economic viability can only be achieved with 16 ha, 21 ha and 70 ha respectively. It was observed that this methodological approach is more complete for decision-making of farmers to use the information published in yearbooks; Furthermore, management of production is essential for the purpose of result on the basis of reflections productivity in the recipe, and the fixed prices.
Keywords: Agribusiness; Cost-volume-profit; Investment analysis; Saccharum spp